2006
DOI: 10.1016/j.neuron.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic Synaptic Excitation and Imbalanced Inhibition Underlying Cortical Intensity Tuning

Abstract: Intensity-tuned neurons, characterized by their nonmonotonic response-level function, may play important roles in the encoding of sound intensity-related information. The synaptic mechanisms underlying intensity tuning remain unclear. Here, in vivo whole-cell recordings in rat auditory cortex revealed that intensity-tuned neurons, mostly clustered in a posterior zone, receive imbalanced tone-evoked excitatory and inhibitory synaptic inputs. Excitatory inputs exhibit nonmonotonic intensity tuning, whereas with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
165
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(193 citation statements)
references
References 56 publications
(112 reference statements)
23
165
1
Order By: Relevance
“…In agreement with others (Wehr and Zador, 2003;Tan et al, 2004;Wehr and Zador, 2005;Wilent and Contreras, 2005;Higley and Contreras, 2006;Wu et al, 2006), we observed that sensory stimulation evokes a stereotypic activation of excitation that was closely followed by a strong inhibition. The stronger inhibitory conductance, relative to the excitatory input, may reflect the larger unitary excitatory post synaptic current (EPSC) of impinging thalamic inputs on inhibitory neurons compared with those that impinge on excitatory cells (Porter et al, 2001;Cruikshank et al, 2007) and the robust firing of fast-spiking neurons during whisker stimulation (Swadlow and Gusev, 2000;Bruno and Simons, 2002).…”
Section: Stereotypic Excitation-inhibition Sequences After Whisker Stsupporting
confidence: 93%
“…In agreement with others (Wehr and Zador, 2003;Tan et al, 2004;Wehr and Zador, 2005;Wilent and Contreras, 2005;Higley and Contreras, 2006;Wu et al, 2006), we observed that sensory stimulation evokes a stereotypic activation of excitation that was closely followed by a strong inhibition. The stronger inhibitory conductance, relative to the excitatory input, may reflect the larger unitary excitatory post synaptic current (EPSC) of impinging thalamic inputs on inhibitory neurons compared with those that impinge on excitatory cells (Porter et al, 2001;Cruikshank et al, 2007) and the robust firing of fast-spiking neurons during whisker stimulation (Swadlow and Gusev, 2000;Bruno and Simons, 2002).…”
Section: Stereotypic Excitation-inhibition Sequences After Whisker Stsupporting
confidence: 93%
“…The resulting non-monotonic response in pyramidal neuron firing is similar to that described in other studies, involving both experimental and modeling contexts (e.g. Wu et al, 2006;Tan et al, 2007;Mikula and Niebur, 2003;Kuhn et al, 2004;de la Rocha and Parga, 2005). However, the underlying mechanisms vary.…”
Section: Non-monotonic Firing Responsessupporting
confidence: 82%
“…An important property in sharpening neural tuning (Wu et al, 2008;Sadagopan and Wang, 2010) and expanding dynamic range (Wu et al, 2006;Tan et al, 2007) is inhibition. Here, we isolated events where firing rate was suppressed below spontaneous firing rate (see Materials and Methods) as a possible window into inhibitory processes ( Fig.…”
Section: Suppressed Responses During Acoustic Stimulationmentioning
confidence: 99%
“…This hypothesis would be easy to test either directly through intracellular recordings or indirectly by observing signatures of inhibition, such as its noted presence at high sound levels (Wu et al, 2006;Tan et al, 2007;Sadagopan and Wang, 2010) or its influence on correlated network activity (Wang, 2010). We did not test sound levels beyond 70 dB SPL except in a few cases to limit awakening the animals.…”
Section: Possible Mechanismsmentioning
confidence: 99%